Coxal combs in the Cydnidae sensu lato and three other related “cydnoid” families – Parastrachiidae, Thaumastellidae, Thyreocoridae (Hemiptera: Heteroptera): functional, taxonomic, and phylogenetic significance - Lis, Jerzy A. (Zootaxa, 2010)
Coxal combs are described for 26 species of 21 genera, representing all currently recognized subfamilies and their tribes within the Cydnidae sensu lato (i.e., Amnestinae; Amaurocorinae; Garsauriinae; Cephalocteinae: Cephalocteini and Scaptocorini; Cydninae: Cydnini and Geotomini s. lato; Sehirinae: Sehirini s. lato). In addition, Thyreocoris scarabaeoides Linnaeus, 1758, and Strombosoma impictum Amyot et Serville, 1843 (Thyreocoridae); Thaumastella aradoides Horváth, 1896 (Thaumastellidae); and Parastrachia japonensis (Scott, 1880), P. nagaensis Distant, 1908, Dismegistus binotatus (Westwood, 1837), and D. fimbriatus (Thunberg, 1783) (currently placed within Parastrachiidae), have also been studied. 22 species were investigated using SEM techniques for the first time. Three basic types of setae, making up the coxal comb, were recognized during the study, i.e., stout setae, gutter-like setae, and scale-like setae. Two main types of the coxal combs are described, i.e., (1) the coxal comb composed of an irregular row of long, apically sharpened, stout setae (Cydnidae: Cephalocteinae: Scaptocorini; and Parastrachiidae), and (2) the coxal comb composed of a regularly aligned row of gutter-like or scale-like setae (all other subfamilies and tribes of the Cydnidae s. lato, Thaumastellidae, and Thyreocoridae). Functional, taxonomic, and phylogenetic significance of the coxal combs is also briefly discussed.